Conferring biological activity to native spider silk: A biofunctionalized protein‐based microfiber. Issue 1 (17th August 2016) - Wu, Hsuan‐Chen; Quan, David N.; Tsao, Chen‐Yu; Liu, Yi; Terrell, Jessica L.; Luo, Xiaolong; Yang, Jen‐Chang; Payne, Gregory F.; Bentley, William E.
ABSTRACT: Spider silk is an extraordinary material with physical properties comparable to the best scaffolding/structural materials, and as a fiber it can be manipulated with ease into a variety of configurations. Our work here demonstrates that natural spider silk fibers can also be used to organize biological components on and in devices through rapid and simple means. Micron scale spider silk fibers (5–10 μm in diameter) were surface modified with a variety of biological entities engineered with pentaglutamine tags via microbial transglutaminase (mTG). Enzymes, enzyme pathways, antibodies, and fluorescent proteins were all assembled onto spider silk fibers using this biomolecular engineering/biofabrication process. Additionally, arrangement of biofunctionalized fiber should in of itself generate a secondary level of biomolecular organization. Toward this end, as proofs of principle, spatially defined arrangement of biofunctionalized spider silk fiber was shown to generate effects specific to silk position in two cases. In one instance, arrangement perpendicular to a flow produced selective head and neck carcinoma cell capture on silk with antibodies complexed to conjugated protein G. In a second scenario, asymmetric bacterial chemotaxis arose from asymmetric conjugation of enzymes to arranged silk. Overall, the biofabrication processes used here were rapid, required no complex chemistries, were biologically benign, and also the resulting engineered silk microfibers were flexible, readily manipulated and functionally active. Deployed here in microfluidic environments, biofunctional spider silk fiber provides a means to convey complex biological functions over a range of scales, further extending its potential as a biomaterial in biotechnological settings. Biotechnol. Bioeng. 2017;114: 83–95. © 2016 Wiley Periodicals, Inc. Abstract : A simple enzymatic assembly approach (using transglutaminase) is exploited to conjugate engineered proteins to spider silk fibers. Organizing these biofunctionalized microfibers provides spatially defined microenvironments that tailor biological responses. Demonstrations include capturing cancer cells from non‐cancer cells and controlling bacterial chemotaxis.